Proposal for the applicability of augmented reality in anatomy laboratories: Application in the Kinesiology career of the Universidad del Alba, Antofagasta (Chile). - Flores-Lucero, Marcelo; González-Llanos, Patricio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Augmented reality allows the user to interact with the physical world. This gives us the possibility of substituting phantoms for digital models. It is intended to determine the functionality of implementing augmented reality technology as a pedagogical resource for the subject of Anatomy. Students will be given a mobile phone app and a picture booklet. With this phone, images will be displayed that will be transformed into augmented reality images that the student will be able to manipulate through their phone. The expected results will focus on promoting the inclusion of M-LEARNING models within the career and the University.